Pengaruh Pola Asuh Orang Tua terhadap Kedisiplinan Pelaksanaan Sholat pada Anak - Muhamad Kumaidi; Evi Febriani; Aulia Senja Dwiputri (Syntax Corporation Indonesia, 2024)
An important role in instilling discipline in children is held by both parents. The discipline of children's worship can be obtained through parents' parenting of their children. Parents vary in teaching their children the discipline of prayer. Some parents use authoritarian methods, where children are forced to pray without providing adequate understanding or explanation. As a result, they tend to perform prayers out of compulsion and lack involvement in making decisions. Permissive or liberal parenting involves parents over-indulging their children and letting them do as they please. It is more likely to give excessive or indifferent attention to their children. If parents neglect their children's worship, especially with regard to prayer and do not encourage or invite them to perform it, then children will neglect worship and act as they wish. If parents over-indulge their children and do not emphasize the importance of praying, these children will become negligent and indifferent towards praying even if their parents ask them to do so. The democratic parenting method is used by the majority of parents. By using this democratic parenting approach, they not only build a good relationship with their children but also give them adequate understanding and explanation of the meaning of prayer. That way, the children.